Ukrainian Student Olympiad on discipline "Histology, Cytology, embryology" (23-24 April 2015) - journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2015)
April 23-24, 2015 at the National Medical University named after O.O. Bogomolets at the Department of Histology and Embryology, the II stage of the Ukrainian Student Olympiad on the discipline "Histology, Cytology, Embryology" took place.